Solo : postmodern explorations - Sassower, Raphael (Lexington Books, 2012)
Solo: Postmodern Explorations provides a postmodern approach to technoscience and economics. Sassower pulls together postmodern motifs and attitudes with his own experience to provide a unique perspective on political history and economics. Solo raises the question of whether it is possible to be an objective observer and what that means for scholarship, especially when it concerns making assessments of other cultures in the developing world. Sassower questions the usefulness of applying external economic measurements on the economic development of these countries.